2024
DOI: 10.3390/su16083329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental, Social, and Governance (ESG) Performance on Corporate Financial Performance in China: Based on the Perspective of Innovation and Financial Constraints

Yiming Xu,
Naiping Zhu

Abstract: This paper analyzes the effects of Environmental, Social, and Governance (ESG) performance on corporate financial performance (CFP), enriching the research on the intrinsic mechanism between ESG and financial performance in developing countries. This study uses a data sample of A-share listed companies in Shanghai and Shenzhen, China from 2009 to 2021, and adopts a two-way fixed effects model research methodology with fixed time and industries to explore the relationship and intrinsic mechanism between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…In Xu and Zhu's (2024) study, the mean ESG grade is 4.268, ranging from 2 to 6. These comparisons indicate that our findings align with previous studies, underscoring overvaluation issues and inconsistent attention to ESG practices among Chinese firms [69]. In addition, the P/B ratios of most firms are below one, indicating that the valuations of Chinese-listed companies are generally high.…”
Section: Descriptive Statisticssupporting
confidence: 88%
See 3 more Smart Citations
“…In Xu and Zhu's (2024) study, the mean ESG grade is 4.268, ranging from 2 to 6. These comparisons indicate that our findings align with previous studies, underscoring overvaluation issues and inconsistent attention to ESG practices among Chinese firms [69]. In addition, the P/B ratios of most firms are below one, indicating that the valuations of Chinese-listed companies are generally high.…”
Section: Descriptive Statisticssupporting
confidence: 88%
“…Most of the firms are profitable, but some of them lose money. Xu and Zhu (2024) found that the average return on assets (ROA) is 0.043, with profitability and loss trends aligning with our findings [69]. The ESG ratings of listed firms range from a high of 7.750 to a low of 1.000, with an average value of 4.173.…”
Section: Descriptive Statisticssupporting
confidence: 82%
See 2 more Smart Citations